Craft knowledge and sustainability : a case study in historical cultivation methods - Sjöberg, Catarina; Löfgren, Maria (FormAkademisk, 2023)
Historical gardens and green cultural environments maintain and transmit parts of our biocultural heritage. The gardener's maintenance and cultivation work affects both the content and our experience of these environments. While modern management methods in many cases are necessary to fulfil requirements for the work environment and efficiency, we want to investigate the extent to which alternative/traditional working methods can contribute with other qualities and with solutions for more sustainable management. Garden and Landscape Crafts bachelor's programme students at the Department of Conservation are practicing a lost craft skill by participating in a comparative cultivation experiment to gain an understanding of historical methods and their relation to the present, as well as the future development and revitalisation of sustainable historical environments.